2011
DOI: 10.1021/es203114q
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Controlled Trial of the Plastic BioSand Water Filter in Cambodia

Abstract: About half of the rural population of Cambodia lacks access to improved water; an even higher percentage lacks access to latrines. More than 35,000 concrete BioSand Water filters (BSF) have been installed in the country. However, the concrete BSF takes time to produce and weighs hundreds of pounds. A plastic BSF has been developed but may not perform to the same benchmarks established by its predecessor. To evaluate plastic BSF performance and health impact, we performed a cluster randomized controlled trial i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
(36 reference statements)
2
31
1
7
Order By: Relevance
“…The findings suggest that the distribution of the filter alone was sufficient to reduce diarrhea outcomes. This finding is consistent with metaregressions by Brown and others,30 Stauber and others,31 and Hunter32 on filter interventions conducted in Asia using ceramic water purifiers (CWPs) and biosand filters (BSFs) 3032. Results from this study suggest that hollow fiber filters can reduce diarrhea prevalence in children under the age of 5 years an additional 6–13% compared with 72% reported in a study on CWPs in Bolivia 14.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings suggest that the distribution of the filter alone was sufficient to reduce diarrhea outcomes. This finding is consistent with metaregressions by Brown and others,30 Stauber and others,31 and Hunter32 on filter interventions conducted in Asia using ceramic water purifiers (CWPs) and biosand filters (BSFs) 3032. Results from this study suggest that hollow fiber filters can reduce diarrhea prevalence in children under the age of 5 years an additional 6–13% compared with 72% reported in a study on CWPs in Bolivia 14.…”
Section: Discussionsupporting
confidence: 88%
“…Compared with the DPR values reported in a study in Cambodia on CWPs (0.58, 95% CI = 0.41–0.82) and iron-rich CWPs (0.65, 95% CI = 0.46–0.93), the diarrheal disease prevalence reductions associated with the PointONE filter seem to be noteworthy 30. Likewise, in another Cambodian study on BSF interventions, a 22% reduction in prevalence of diarrhea was observed, still markedly lower than the effect sizes reported with the PointONE filter 31. Lastly, in a meta-analysis on 33 reports from 21 different countries conducted by Clasen and others,21 chlorination and flocculation disinfection studies estimating the intervention effect in children under 5 years of age using longitudinal prevalence ratios showed that they were less effective (0.91, 95% CI = 0.82–1.02 and 0.42, 95% CI = 0.13–1.37, respectively).…”
Section: Discussionmentioning
confidence: 86%
“…However, these results do not document an ability to reduce diarrheal disease in households with a BSF, which has been previously reported, including in other trials of the Hydraid plastichousing BSF. 9,12,13,32 The BSF in this trial was simultaneously tested in Cambodia with a similar study designthey found that, in households with a Hydraid plastic-housing BSF, participants had a 59% reduced risk of diarrheal disease (IRR = 0.41, 95% CI = 0.24, 0.69) and significant improvements in their water quality. 32 It is important to note that, outside of this study, International Aid only promoted the Hydraid plastic-housing BSF in conjunction with safe storage and post-filtration chlorination.…”
Section: Discussionmentioning
confidence: 99%
“…Both the concrete and plastic BSF models have recently been shown to improve microbiological water quality in the home and reduce diarrheal disease [13,14,15]. In 2008, researchers conducted an RCT of the plastic BSF in Santa Rosa de Copan, Honduras [13].…”
Section: Introductionmentioning
confidence: 99%